PTU-088 Non-coeliac Gluten Sensitivity Can Be Present In Inflammatory Bowel Disease, Not Just Irritable Bowel Syndrome. (9th June 2014) - Aziz, I; Winfield, SN; Kelsall, A; Rugg, N; Pearson, K; Priest, J; Sanders, DS
Abstract : Introduction: Self-reported gluten sensitivity (GS) commonly occurs in the absence of coeliac disease, and is termed non-coeliac gluten sensitivity (NCGS); a controversial, heterogeneous, clinical entity perceived by some to belong to the spectrum of irritable bowel syndrome (IBS) due its lack of putative biomarkers. Aims: We evaluated whether NCGS may be reported in organic gastrointestinal pathologies. Methods: A validated questionnaire screened for self-reported GS in four patient groups (cohort A); i) IBS, ii) crohns disease (CrD), iii) ulcerative colitis (UC) and iv) gastro-oesophageal reflux disease (GORD). In addition, the prevalence of organic pathology in a seperate group presenting and diagnosed with NCGS was also determined (cohort B). Results: Cohort A: 59 cases of IBS (mean-age 32.7 yrs, 80% female), 75 CrD (mean-age 47.1 yrs, 59% female), 71 UC (mean-age 43.2 yrs, 68% female) and 109 GORD (mean-age 51.7 years, 61% female); p value for age < 0.001 and gender 0.05. The presence of GS was 42.4% for IBS, 29% CrD, 25.3% UC and 18.3% for GORD. Adjusting for age and sex, IBS individuals were significantly more likely to self-report GS compared to individuals with GORD (p 0.02, OR 2.56, C. I 1.15–5.73). However, there was no difference in self-reported GS between IBS, CrD or UC. In CrD the presence of strictures (p 0.04, OR 3.12, C. I 1.03–9.45) and CrD-activity index > 220 (p.0001, OR 8, C. I 2.45–2.62) were predictors of self-reporting GS. In contrast, a CrDAI score < 150 was supportive of not being GS (p 0.002, OR 5.35, C. I 1.8–15.9). The simple colitis activity score did not influence the presence or absence of GS in UC. Cohort B: Analysis of 200 NCGS patients (mean-age 39.1 yrs, 83% female) shows that 3% were subsequently found to have organic pathology (two cases of UC, one case each of CrD and pyloric stricture). Conclusion: NCGS is not exclusive to IBS and can also be seen in established organic gastrointestinal pathologies, such as inflammatory bowel disease. Its presence may be reflecting severe and stenotic disease. Occasionally, NCGS may be the first presentation of organic pathology. Disclosure of Interest: None Declared.